“Time of Care”: a narrative medicine project with applied theatre (Altre Modernità, 2024)
As is well known, the first wave of the pandemic hit the city and province of Bergamo hard. Two years later, a group of emergency room professionals of the Papa Giovanni XXIII hospital in Bergamo decided to work with the theatre to tell their story and re-elaborate trauma. Guided by an applied theatre professional, the group worked for a whole year on their experience on the front line during the pandemic to stage the play “Silent Days, Sleepless Nights”, which debuted in March 2023. The two authors of this contribution followed the theatre workshop with a collaborative ethnography. Of particular interest is that one of them, being a theatre professional, also participated in constructing the play as a dramaturge. This contribution reflects on the theatre workshop as a place for the re-elaboration of traumatic memories and as a place for the construction of a new collective memory. Using the framework of Narrative Medicine, the paper shows how theatre techniques allow collective memory to resonate with traumatic memories by giving them a different meaning. Participants on stage and in the theatre room re-read the traumatic memory within a broader frame of meaning that includes the collective possibility of sharing, processing and healing from trauma.
Keywords: Narrative Medicine; Applied Theatre; Bergamo; COVID-19; Silent Days, Sleepless Nights; Time of Care